Similarities and differences in guidelines for the management of pancreatic cysts - Lanke, Gandhi (World J Gastroenterol, 2020)
Accurate diagnosis of Pancreatic cysts (PC) is key in the management. The knowledge of indications for surgery, the role of endoscopic ultrasound-guided fine needle aspiration, cyst fluid analysis, imaging, and surveillance of PC are all important in the diagnosis and management of PC. Currently, there are many guidelines for the management of PC. The optimal use of these guidelines with a patient-centered approach helps diagnose early cancer and prevent the spread of cancer.